Estatística no ensino médio: uma proposta teórico-metodológica fundamentada na teoria da aprendizagem significativa - Quedi, Rejane Padilha (2019)
The present investigation starts from the perception that, when entering a college course, students present significant conceptual gaps, which is often responsible for a high failure rate in the disciplines of the Statistics Area. The reproofs confirm the lack of understanding and mastery of these concepts, both for use in the discipline of Statistics as for use in situations of interpretation and analysis of data in other disciplines. In this context, it is evident the need to develop strategies and teaching methodologies that can promote meaningful, long-lastingand deep learnings in Basic Education. With this perception, the following question was formulated: How can a didactic sequence of basic concepts of Statistics be a potentially significant material for the teaching of the area? To answer this question, a didactic sequence was elaborated to approach the basic concepts of Statistics, which was structured according to the assumptions of David Paul Ausubel's Theory of Significant Learning, divided into five meetings and implemented with a group of eight Academics of the sixth level of the course of Mathematics – Degree of the University of Passo Fundo, in the discipline of Methodology of the Teaching of Mathematics III. The research, classified as qualitative and participant, was effected based on the analysis of semi-structured interviews with the students and in the records made by the researcher in the logbook. The collected data were analyzed in order to show if the didactic sequence is a potentially significant material in the perception of the future Mathematic steachers, according to the following categories: ability to relate the contents studied with the previous knowledge of the students; promotion of progressive differentiation and integrative reconciliation; materials used; structure of the proposal; participation and commitment in the activities. The results indicate that the proposed didactic sequence can be considered a potentially significant material in the perception of the future teachers of Mathematics, since it was able to instigate them to seek more knowledge and made possible the perception of the importance of the use of creative strategies for the study of the area in High School. Finally, an educational product that brings together the material used in the meetings and the didactic sequence developed accompanies this dissertation. This product is available at website:<http://educapes.capes.gov.br/handle/capes/552764>.